Influence of parasitism on trace element contents in tissues of red fox (Vulpes vulpes) and its parasites Mesocestoides spp. (Cestoda) and Toxascaris leonina (Nematoda) - Jankovská, Ivana; Miholová, Daniela; Bejcek, Vladimír; Vadlejch, Jaroslav; Sulc, Miloslav; Száková, Jirina; Langrová, Iva (Archives of environmental contamination and toxicology, 2010)
Bioaccumulation of cadmium, chromium, copper, manganese, nickel, lead, and zinc in 56 foxes (Vulpes vulpes) and their parasites Mesocestoides spp. (Cestoda) and Toxascaris leonina (Nematoda) was studied. The levels of heavy metals were determined in the livers and kidneys of the animals depending on parasitism in the following ranges: Pb, 0.029-3.556; Cd, 0.055-9.967; Cr, 0.001-0.304; Cu, 4.15-41.15; Mn, 1.81-19.94; Ni: 0.037-0.831; Zn, 52.0-212.9 microg/g dry weight (dw). Cd in parasites (0.038-3.678 microg/g dw) were comparable with those in the livers of the host and lower than in the kidneys (0.095-6.032 microg/g dw). Contents of Pb, Cr, Cu, Mn, Ni, and Zn in cestodes were predominantly higher than those in the kidney and liver of the host. Median lead levels in Mesocestoides spp. (45.6 microg/g dw) were 52-fold higher than in the kidney and liver of the red fox (Vulpes vulpes) infected by both parasites and median Pb values in T. leonina (8.98 microg/g dw) were 8-fold higher than in the tissues of the parasitized red fox. Bioaccumulation factors of copper, zinc, nickel, and manganese are lower than those of lead and mostly range from 1.9 to 24 for Mesocestoides spp. and from 1.5 to 6 for nematode T. leonina depending on the tissue of host and element. A significant decrease in the content of Pb was found in the kidney of animals infected by T. leonina (0.260 microg/g dw) as well as those infected by Mesocestoides spp. (0.457 microg/g dw) in comparison with the lead content (0.878 microg/g dw) in the kidneys of the nonparasitized red fox. Regardless of a bioaccumulation of copper and manganese in the parasites, a significant increase of the concentrations of Mn and Cu was observed in the host's livers infected predominantly by Mesocestoides spp.
Keywords: ledviny; cestodózy; Environmental Monitoring; lišky; Environmental Pollutants; Metals, Heavy; zvířata; látky znečišťující životní prostředí; Mesocestoides; parazitární nemoci u zvířat; mužské pohlaví; Toxascaris; ženské pohlaví; Female; Liver; Nematode Infections; Animals; nematodózy; Kidney; Parasitic Diseases, Animal; Foxes; játra; těžké kovy; Male; monitorování životního prostředí; Cestode Infections